2013
DOI: 10.4236/ajps.2013.48a002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Positions of QTLs Conferring Resistance to <i>Xanthomonas campestris</i> pv. <i>campestris</i> in <i>Brassica oleracea</i>

Abstract: Black rot, caused by Xanthomonas campestris pv. campestris (Xcc) is possibly the most important disease of Brassica worldwide. To compare chromosomal positions of Xcc resistance loci in Brassica oleracea between the present and published studies and to develop marker assisted selection (MAS) to resistance against Xcc race 1, we constructed a B. oleracea map, including pW, pX and BoCL markers that were closely linked to previously reported Xcc resistance QTLs. We also analyzed Xcc resistance QTLs by improving o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 33 publications
(74 reference statements)
2
30
1
Order By: Relevance
“…This result is consistent with previous report as described the race-specific resistance against Xcc in Brassica species by Ignatov et al (1998). Besides, Tonu et al (2013) also reported black rot resistance in B. oleracea in particular to Xcc race 3 and race 5. It should be noted that the phenotypic screening results revealed SCNU-C-4059 as resistant lines against race 7 but none of the tested markers correlated with the phenotype except BoGMS0971 which showed only 36% adaptability with bioassay results (Table 3).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is consistent with previous report as described the race-specific resistance against Xcc in Brassica species by Ignatov et al (1998). Besides, Tonu et al (2013) also reported black rot resistance in B. oleracea in particular to Xcc race 3 and race 5. It should be noted that the phenotypic screening results revealed SCNU-C-4059 as resistant lines against race 7 but none of the tested markers correlated with the phenotype except BoGMS0971 which showed only 36% adaptability with bioassay results (Table 3).…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the tested polymorphic marker BnGMS301 located on chromosome C01. Tonu et al (2013) found XccBo(Reiho)2 on chromosome C08 as the major locus for black rot resistance in cabbage and the SSR marker BoGMS0971 was closely linked to it. The remaining two SSR markers namely BoESSR291 and OI10G06 were linked to the minor QTLs (BRQTL-C3 and BRQTL-C6, respectively) The Brassica oleracea Genome Database (Bolbase).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The available sources of resistance are limited and often race-specific (Ignatov et al, 1998;Tonu et al, 2013). For the species B. oleracea (genome CC), resistance for predominant races is rare or only partial.…”
Section: Introductionmentioning
confidence: 99%